THE EFFECTIVENESS OF FISHBOWL TO STUDENT’ SPEAKING ABILITY AT SMA NEGERI 1 MANADO - Karouw, Fabiola; Tuerah, Ignatius J. C.; Hampp, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Speaking is a mode of communication that includes the creation, transmission, and receiving of ideas. Unfortunately, most students taught that they are not able to speak English well enough. The usage of teacher-teaching methods may be the root of the issues. In certain cases, the instructor maintains control over the majority of the class by providing a few opportunities for students to practice speaking in front of the group. Determining if Fishbowl is helpful for improving students’ speaking ability is the aim of this study. The case was conducted in the SMA Negeri 1 Manado. Thirty-six twelfth-grade students served as the subjects of this investigation. The researcher carried out a quantitative investigation using a pre-experimental design and a single group for the pre- and post-tests. During the process of gathering data, the researcher employed an experiment. The study employed two tests: a pre-test and a post-test. The format of the pre- and post-tests is the same, but the subjects are not. According to the study’s results, the mean score of the post-test (86,19) was higher than the pre-test’s (32,91). This suggests that pupils’ speaking abilities were enhanced by the Fishbowl approach.